A Randomized Controlled Trial of Antithrombin Supplementation During Extracorporeal Membrane Oxygenation. Issue 11 (November 2020) - Panigada, Mauro; Cucino, Alberto; Spinelli, Elena; Occhipinti, Giovanna; Panarello, Giovanna; Novembrino, Cristina; Consonni, Dario; Protti, Alessandro; Lissoni, Alfredo; Arcadipane, Antonio; Pesenti, Antonio; Grasselli, Giacomo
Abstract : Objectives: Supplementation of antithrombin might decrease the amount of heparin needed to achieve a given anticoagulation target during extracorporeal membrane oxygenation. However, exogenous antithrombin itself may increase the risk of bleeding. We conceived a study to evaluate the effect of antithrombin supplementation in adult patients requiring venovenous extracorporeal membrane oxygenation for respiratory failure on heparin dose, adequacy of anticoagulation, and safety. Design: Prospective randomized controlled trial. Setting: ICUs of two Italian referral extracorporeal membrane oxygenation centers. Patients: Adult patients requiring venovenous extracorporeal membrane oxygenation for severe respiratory failure and unfractionated heparin for systemic anticoagulation. Interventions: Before extracorporeal membrane oxygenation start, patients were randomized to either receive antithrombin concentrate to maintain a plasmatic level 80–120% (treatment) or not (control) during the extracorporeal membrane oxygenation course. Measurements and Main Results: The primary outcome was the total amount of heparin required to maintain activated partial thromboplastin time ratio 1.5–2. Secondary outcomes were anti-factor Xa, the incidence of hemorrhagic and thrombotic events, and the amount of blood products transfused. Twenty-four patients in the treatment group and 24 in the control group were included in the intention-to-treat analysis. Antithrombin was 109.5% (93.0–123.0%) in the treatment group and 84.0% (68.5–98.0%) in the control group ( p = 0.001). Supplementation of antithrombin did not decrease heparin dose (13.5 international units/kg/hr [9.6–17.9 international units/kg/hr] vs 15.1 international units/kg/hr [10.7–18.3 international units/kg/hr] in the treatment and control group, respectively; p = 0.33) and anti-Factor Xa levels (0.4 international units/mL [0.3–0.5 international units/mL] vs 0.3 international units/mL [0.2–0.5 international units/mL] in the treatment group and control group respectively; p = 0.65). Bleeding, blood product transfusions, and thrombosis were not different in the two groups. Conclusions: Antithrombin supplementation may not decrease heparin requirement nor diminish the incidence of bleeding and/or thrombosis in adult patients on venovenous extracorporeal membrane oxygenation. Abstract : Supplemental Digital Content is available in the text.